Pengaruh Lama Pengomposan Tandan Kosong Kelapa Sawit (Tkks) Terhadap Pertumbuhan Dan Perkembangan Bibit Kelapa Sawit (Elaeis guineensis jacq) - Azlansyah, Boby; Silvina, Fetmi; ', Murniati (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
The purpose of this research to get the receptable of long composting palm empty fruit bunches as mixed of media to support the growth and development of oil palm seedlings. This research was experiment and used Completely Randomized Design (CRD) consisting of 3 treatments with 6 replications, so there are 18 experimental units. Each unit consists of two plants. The treatment were:                 A1 = Composting two weeks, A2 = Composting four weeks, and A3 = Composting six weeks. The result of this research shown that the use of compost empaty fruit bunches with long composting influential to the seedling height and hump diameter, during composting 2, 4, and 6 weeks show indicates the number of leaf midrib, long of leaf, crown root ratio, dry weight of seedlings but during the six weeks long composting show higer vielt to get better growth and development of oil palm seedlings can use empaty fruit bunches.   Keywords: long composting, palm empty fruit bunches, oil palm seedlings.